Pengaruh Media Promosi Kesehatan Terhadap Pengetahuan Nutrisi Pada Penderita Hipertensi Peserta Prolanis di Puskesmas Banda Sakti Kota Lhokseumawe - Zara, Noviana; Munthe , Kania Wiritanaya; Nadira , Cut Sidrah (Journal of Pharmaceutical and Sciences, 2025)
Hypertension is known as the "silent killer," responsible for over 10 million deaths worldwide each year. In Indonesia, there are more than 1 million cases of hypertension, yet only 38.2% of sufferers receive healthcare services according to standards. Data from the Aceh Health Office in 2022 recorded over 44,000 cases of hypertension in Lhokseumawe City. One of the factors contributing to the increase in hypertension cases is the low level of public knowledge regarding the management of this condition. Hypertension management can be achieved through a low-salt diet, low-cholesterol diet, and high-fiber diet. One of the efforts to enhance knowledge about proper nutrition for hypertension patients is through health promotion using audiovisual media, which presents information in both visual and auditory forms. This study aims to identify the effect of health promotion media on nutrition knowledge in hypertension patients who are participants in the Chronic Disease Management Program (Prolanis) at Banda Sakti Health Center. The research employed a quasi-experimental design with a one-group pretest-posttest design, involving 40 Prolanis participants. The results show that the majority of respondents were elderly, female, unemployed, and had completed high school. After the intervention, there was a 92.5% increase in knowledge about hypertension nutrition, with the knowledge categorized as good. Statistical analysis using the Wilcoxon test revealed a significant effect of audiovisual media on improving hypertension nutrition knowledge, with a p-value < 0.05. The conclusion of this study is that health promotion media has a significant effect on improving nutrition knowledge in hypertension patients who are participants in the Prolanis program at Banda Sakti Health Center.